The Practical Utility of Imidazolium Hydrogen Sulfate Ionic Liquid in Fabrication of Lignin-Based Spheres: Structure Characteristic and Antibacterial Activity - Stanisz, Małgorzata; Klapiszewski, Łukasz; Dobrowolska, Anna; Piasecki, Adam; Czaczyk, Katarzyna; Jesionowski, Teofil (Frontiers in Chemistry, 2022)
In this study, lignin-based spherical particles (Lig-IL) with the use of 1-(propoxymethyl)-1H-imidazolium hydrogen sulfate were prepared in different biopolymer and ionic liquid (IL) weight ratios. The application of IL during the preparation of spherical particles is an innovative method, which may be beneficial for further applications. The particles were obtained with the use of soft-templating method and its chemical, structural and morphological characterization was performed. The spherical shape of products and its size was confirmed with the use of scanning electron microscopy (SEM) images and the particle size distribution results. The attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectra were analyzed to identify functional groups of all precursors and produced material and it was confirmed, that all materials exhibit characteristic hydroxyl and carboxylic groups, but the presence of carbonyl group was detected. Moreover, the zeta potential analysis was performed to evaluate electrokinetic behaviour of obtained materials. It was confirmed, that all materials are colloidally stable in pH above 4. Produced lignin-based spherical particles were used for evaluation of its antibacterial properties. Particles were tested against Staphylococcus aureus (S. aureus), a gram-positive bacterium and against Escherichia coli (E. coli), a gram-negative one. It was observed, that only the material with the highest addition of IL showed the antibacterial properties against both strains. However, all prepared materials exhibited the antibacterial activity against a gram-positive bacterium.